(3QSGdI aj ebOGQ GdSfI GdSQeOjIs
(3ChdgG (B:s
(3aUd ai HjGf ebOGQ GdSfI GdSQeOjI hJYjjf GdCjGe GdEdgjI efgG jhe GdbjGeI hHYO aEf MbjbI GdPGJ GdEdgjI ef MjK gi gi EeJOGOgG CYfi eOI HbGFgG s
(3BNQgG (B:s
(3hef JQbi Edi GdMVQI GdhGMOjI NQL ef CjGe GdQHhHjI Edi GdCjGe GdEdgjI ai GdSfI GdSQeOjI JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B32s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3Gdadcs